Análise do clima organizacional na integração de duas empresas do setor varejista: identificando dificuldades e possibilidades de melhoria - Ishiba, Simone [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In 2010 two retailers signed an association agreement to gain an advantage in the market, however this association has promoted many changes within the companies. So this study had the objective to analyze the organizational climate, in the integration of companies context, in order to early detect deficiencies that could pose risks to the process of integration. The results collected from the questionnaires revealed the perceptions and expectations of employees regarding the integration of companies and their level of satisfaction with the organization, in addition, the data obtained from interviews allowed us to understand and to find some causes to the level of satisfaction presented by employees. The results made possible to identify strengths as the company‟s image, points of failure in communication and training and dissatisfaction with the workload, then some actions were suggested with the intention to achieve greater engagement and commitment of employees and consequently contribute to the success of the Integration Program. The conclusion of this study is that the changes promoted by the integration of companies impacted in the organizational climate and increased employees dissatisfaction

Em 2010 duas empresas varejistas assinaram um acordo de associação com o intuito de obter vantagem no mercado, contudo esta associação promoveu inúmeras mudanças dentro das empresas. O presente trabalho teve então como objetivo analisar o clima organizacional, no contexto de integração de empresas, com o intuito de detectar precocemente deficiências que poderiam impor riscos ao processo de integração. Os resultados provenientes dos questionários coletados mostraram as percepções e expectativas dos colaboradores com relação à integração e o seu nível de satisfação com relação à organização, além disso, os dados obtidos das entrevistas permitiram entender e encontrar algumas causas para os níveis de satisfação apresentados pelos colaboradores. A análise dos resultados possibilitou identificar pontos fortes como a imagem da empresa, pontos de deficiência na comunicação e no treinamento e insatisfação com relação à carga de trabalho, então foram sugeridas algumas medidas com o intuito de obter maior engajamento e comprometimento dos colaboradores e conseqüentemente contribuir para o sucesso do Programa de Integração. Concluiu-se com o trabalho que as mudanças promovidas pela integração de empresas impactaram no clima organizacional e aumentaram a insatisfação entre os colaboradores
Keywords: Clima organizacional; Qualidade de vida no trabalho; Desenvolvimento organizacional; Organizacional climate; Integration of companies; Level of satisfaction